Pengaruh Brand Image dan Promosi Terhadap Minat Beli Konsumen Vitamin C Vitalong C pada PT. Bernofarm Cabang Semarang - Rini, Nita Setya (Universitas Slamet Riyadi, 2021)
This study aims to determine the significant influence between: (1) Brand image and (2)promotion on consumer buying interst in vitamin c Vitalong C at Pt. Bernofarm Semarang. The population in this study were 100 customerss Vitalong C in Semarang. In this study, the sample taken was a saturated sample (census), that is, all populations were sampled. The analysis technique uses multiple linear regression with the classical assumption test. The results of the analysis are (1) Brand Image and Promotion variables is valid. The results of the reliability test were reliable, (2) the multicollinearity test passed the test, passed the heteroscedasticity test, passed the autocorrelation test, and passed the normality test. The results of the analysis show: brand image and promotion a significant effect on consumer buying interst in vitamin C Vitalong C at. Pt Bernofarm Semarang. Keywords:brand image, promotion and consumer buying interst